CIVILIZATION SCENARIOS OF DEVELOPMENT OF RUSSIA - A. N. Kharin (Модернизация, инновация, развитие, 2016)
In the modern world plays an important role civilization factor. In this connection before Russia a task stands forming of civilization identity. A problem consists in that, that exists a few scenarios of civilization development. To their consideration and this article is devoted.